2015
DOI: 10.1371/journal.pone.0134492
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Wnt3a and Wnt5a Signaling Pathway in the Lung from Rats with Endotoxic Shock

Abstract: Septic shock is a syndrome with severe hypotension and multiple organ dysfunction caused by an imbalance between pro-inflammatory and anti-inflammatory response. The most common risk factor of acute lung injury is severe sepsis. Patients with sepsis-related acute respiratory distress syndrome have higher mortality. Recent studies reveal regulatory roles of Wnt3a and Wnt5a signaling in inflammatory processes. Wnt3a signaling has been implicated in anti-inflammatory effects, whereas Wnt5a signaling has been post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
9
0
3
Order By: Relevance
“…In contrast, Wnt5a, Fzd5, total CaMKII, and phosphorylated CaMKII were upregulated, indicating that Wnt5a dependent, pro-inflammatory Ca 2+ /calmodulin signaling is strongly activated in endotoxemic rats (93). These findings are corroborated by Villar et al who observed that lungs of septic animals and humans are characterized by acute lung inflammation, collagen deposition, and marked increase of Wnt5a (94).…”
Section: Opposing Roles Of Wnt5a and Wnt/beta-catenin Signaling In Inmentioning
confidence: 99%
“…In contrast, Wnt5a, Fzd5, total CaMKII, and phosphorylated CaMKII were upregulated, indicating that Wnt5a dependent, pro-inflammatory Ca 2+ /calmodulin signaling is strongly activated in endotoxemic rats (93). These findings are corroborated by Villar et al who observed that lungs of septic animals and humans are characterized by acute lung inflammation, collagen deposition, and marked increase of Wnt5a (94).…”
Section: Opposing Roles Of Wnt5a and Wnt/beta-catenin Signaling In Inmentioning
confidence: 99%
“…En este estudio utilizamos el modelo de inflamación sistémica producida por LPS E. coli, debido a que la administración vía sistémica del mismo ocasiona una reacción inflamatoria rápida, 25 mediada principalmente por los receptores tipo Toll 4 (TLR-4), que al ponerse en contacto con el LPS ocasionan una respuesta inflamatoria rápida con alteraciones fisiológicas [25][26][27] como taquicardia, hipotensión arterial sistémica, hipertensión pulmonar y disminución del GC como se observó en este estudio. También utilizamos este modelo porque la infusión del LPS a través de un catéter venoso central tiene la ventaja de que los pulmones sean el primer endotelio afectado y ocasione cambios a nivel pulmonar; 28,29 sin embargo, su uso no siempre ocasiona SIRA como se observó en este estudio y concuerda con lo descrito por Müller-Leisse y su grupo.…”
Section: Discussionunclassified
“…www.medigraphic.org.mx durante las primeras horas porque el LPS E. coli al producir la respuesta inflamatoria ocasiona vasodilatación y disminución de las RVS. [25][26][27] Sin embargo, retornaron sus valores basales después de aplicar los diferentes modos ventilatorios por los efectos provocados sobre la presión intratorácica ocasionados por cada modo ventilatorio, como describieron anteriormente Osiovich, 18 Karmrodt, 19 Traverse, 36 David, 37 y Smailys 38 y sus respectivos grupos de investigación. Los incrementos en las PMAP y RVP observados en los modos ventilatorios de APRV y VAFO probablemente fueron originados porque además del daño provocado por el LPS E. coli, estos modos ventilatorios ocasionaron incrementos en la presión transpulmonar y, como consecuencia de estos cambios, en la precarga y poscarga cardíaca, lo cual concuerda con lo descrito por otros autores que han estudiado el uso de la AMV en modo APRV y VAFO en pacientes con SIRA 14,33 y en modelos animales de VILI 40 y sepsis.…”
Section: A B C Dunclassified
See 1 more Smart Citation
“…The proposed mechanism might constitute one of the possible molecular mechanisms underpinning the endotoxin tolerance theory. If such homeostatic feedback mechanism is indeed operational in human myeloid cells during infections, cancer, and inflammation merits further investigation in the clinical setting 4,20,38,39 .
Fig. 6Model for Wnt5a as a tolerance-associated molecular pattern (TAMP).
…”
Section: Discussionmentioning
confidence: 99%